Peer-Centered Versus Standard Physician-Centered Video Counseling for Midurethral Sling Surgery: A Randomized Controlled Trial. Issue 8 (August 2020) - Krantz, Tessa E.; Rogers, Rebecca G.; Petersen, Timothy R.; Dunivan, Gena C.; White, Amanda B.; Madsen, Annetta M.; Jeppson, Peter C.; Ninivaggio, Cara S.; Cichowski, Sara B.; Komesu, Yuko M.
Abstract : Objectives: Peer counseling may improve upon provider counseling and enhance patient preparedness for midurethral sling (MUS) surgery. We aimed to compare the impact of peer-centered versus standard preoperative video counseling by assessing patient preparedness for MUS surgery. Methods: Women undergoing MUS were randomized to view either a peer-centered (PEER) or standard physician preoperative counseling video (PHYS). The PEER video featured a woman who had undergone MUS surgery and included the standard risks and benefits as well as additional information identified in prior work as important to patients. The PHYS video featured a surgeon discussing risks and benefits. Patients viewed either video at their preoperative visit and completed the Patient Preparedness Questionnaire (PPQ), Surgical Decision Satisfaction, Decisional Regret Scale, and the Urogenital Distress Inventory Short Form. Patients then underwent standard in-person surgeon counseling. Sessions were timed and compared with historical timed sessions. Our primary outcome was between-group differences in 6-week postoperative PPQ scores. Results: Patient Preparedness Questionnaire scores did not differ between groups (postoperative PPQ scores: median [interquartile range], 95 [84, 100] vs 92 [80, 100]; P =0.50). The PEER group reported higher decisional regret (15 [0, 28.75] vs 0 [0, 10], P =0.02) and less symptom improvement on Urogenital Distress Inventory Short Form change scores compared with the PHYS group (47.2 [37.2, 62.5] vs 36.1 [16.5, 50], P =0.03); secondary outcomes were not different between groups. In-person counseling times decreased after watching either video compared with the institution's historical standard (8:27 minutes [08:56, 17:14] vs 11:34 minutes [5:22, 13:07]; P < 0.005). Conclusion: Patient preparedness did not differ between groups. Decision regret did not differ between groups once adjusted for urinary symptoms.